Acute generalised exanthematous pustulosis associated with upadacitinib treatment - Thandiwe Banda; Sanaa Butt; Madhavi Maheshwari; Moumita Chattopadhyay (Skin Health and Disease)
Abstract Acute generalised exanthematous pustulosis (AGEP) is a rare drug‐induced pustular eruption characterised by the rapid onset of superficial pinhead pustules. We discuss the case of a 27‐year‐old man who presented with a generalised pustular eruption on the neck, trunk and limbs. He commenced upadacitinib for the treatment of atopic dermatitis (AD) 6 months before developing the rash, and the dose was increased from 15 to 30 mg daily, 3 months prior. His only other medication was oral terbinafine, for suspected tinea corporis, which was initiated 1 month before developing the pustular eruption. Laboratory investigations showed a mildly raised CRP 25 mg/L, neutrophilia 8.22 10 × 9/L, and a mildly raised ALT 46 U/L. A skin biopsy showed subcorneal pustules and a few scattered keratinocytes. Upadacitinib and terbinafine were suspended and the pustular eruption resolved. Updacitinib was reintroduced 3 weeks later as the rash was thought to be due to terbinafine and the rash recurred. He was diagnosed with AGEP secondary to upadacitinib. Upadacitinib is a selective JAK inhibitor that is increasingly used for the management of AD and clinicians should be aware that AGEP is a rare but severe adverse effect.